Determinan Perilaku Seks Pranikah pada Remaja Menurut Teori Health Belief Model (HBM): Studi Literatur Tahun 2019-2024 (Inovasi Kesehatan Global, 2026)
Premarital sex is sexual intercourse outside of legal or religious marriage. This behavior can cause various problems such as sexually transmitted diseases, unplanned pregnancies, and encourage early marriage. Analyzing the determinants of adolescent premarital sex based on the Health Belief Model. Using a literature review approach, this study analyzes several academic references such as journals, books, encyclopedias, and others that discuss the topic of premarital sex among adolescents based on the Health Belief Model (HBM) Theory. This study uses seven journals, with sources from the last six years. The study began in October-November 2025. Based on the analysis, there is a relationship between perceived susceptibility, perceived severity, perceived benefits, perceived barriers, perceived self-efficacy, cues to action, and premarital sex behavior among adolescents. The conclusion shows that in all seven studies, the main components of HBM are significantly related to this behavior. For adolescents, it is recommended to better understand premarital sex behavior by seeking appropriate information and selecting positive friends and social environments so as not to be influenced by negative things or the urge to engage in premarital sex behavior.